Modal Sosial Masyarakat Dalam Pengelolaan Hutan Rakyat di Kecamatan Poso Pesisir - Isnain, Moh.; Rachman, Imran; Sudirman, Sudirman (Mitra Sains, 2024)
In Indonesia, commercial management of community forests began several hundred years ago. This research aims to measure the level of social capital in community forest management, and analyze its influence on community forest performance. The research was carried out using a survey method. Two villages in one district were chosen purposively. Respondents were 60 people that randomly selected from each village. The results of the research reveal that the level of social capital of the two communities in community forest management is classified as different. High social capital has facilitated the revival of good community forest performance, which is characterized by high levels of community forest productivity, as well as continuing sustainable management of community forests, the benefits of regulations. fair management and cost efficiency of community forest management. Strong social capital drives better performance. This research concludes that community social capital in managing community forests in Toini Village is relatively high, while in Betania Village it is low. Considering the differences in social capital that exist in society, the author suggests the need to increase parties, especially the government, to support forest management through increasing roles, facilitating the expansion of social networks, and strengthening the implementation of rules to the community.